SPATIAL KNOWLEDGE MANAGEMENT DAERAH RUANG TERBUKA HIJAU UNTUK PERENCANAAN STRATEGIS DAERAH URBAN (STUDI KASUS: KOTA PONTIANAK) - Faisal, M Fahmi (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Strategic planning of urban areas such asdevelopment planning is an important thing to beconsidered by the government and relevantstakeholders in carrying out the construction ofthe city of Pontianak. Management activities andgeographical mapping that includes profiles, information and description of the total area ofgreen and open space, residential areas and nonresidentialareas is necessary for the analysisneeds that produces output in the form ofrecommendations for consideration ofdevelopment plan policy makers in evaluating andintervening development program, which was heldin Pontianak city. Spatial Knowledge Managementresearch area of green and open space in the cityof Pontianak using small area estimationapproach in analyzing and generating outputinformation in the scope of the sub-sample of thesmallest areas. Results of analysis can identifyingthe possibility of development system thatorganized in the form of manipulation of maps in the current system and provide an alternativerecommendation at the level of input, process andoutput. Spatial Knowledge Management area ofGreen and Open Space-Based on GeographicInformation System is designed to facilitate theimplementation of development in the form ofmanipulation of maps inside the system and toanalyze the data into processing information. Inaddition the system is designed to be amanagement tool in decision making for theimplementation of development activities in thecity of Pontianak. The output of the system are theconsolidated graphs, maps and neighborhood areaplanning recommendations generated when theuser is manipulating the map with the knowledgebased which has been designed on the system. TheKnowledge Based which is designed has aprobability to rearrange by the user in accordancewith the government regulations that areapplicable when the system is used. The result ofthis study is strategic planning recommendationsin the form of urban development plan, which is expected to help the government as policy makersin determining the type of area that can be builton an area in the city of Pontianak.